Manajemen Peningkatan Mutu Madrasah di Pondok Pesantren Nurmadani NW Montong Lisung - Purna Wirawan; Muhammad Thohri; Yudin Citriadin (MANAZHIM, 2023)
The low quality of education in Indonesia is actually a discussion that has existed for a long time, but until now the problem of education quality has not been resolved. Quality education is the hope and demand of all education stakeholders. Everyone will certainly prefer to study at institutions that have good quality. On this basis, madrasas/educational institutions must be able to provide good service and quality so that they are not left behind and are able to compete with other institutions. This study used a qualitative approach, data were collected by interviews and observations with documentation. Data were analyzed using data reduction, data condensation, data presentation and data verification. This research resulted in (1) Quality improvement management planning at the Nurmadani NW Montong Lisung Islamic Boarding School based on national education standards, but in this study it only examined one of these national education standards, namely education staff standards. (2) The organization of quality improvement management at the Nurmadani NW Montong Lisung Islamic Boarding School is in accordance with the organizational structure because each administrator works according to their respective duties and functions. (3) Motivation in carrying out quality improvement management at the Nurmadani NW Montong Lisung Islamic Boarding School by fostering mastery of the material, mastering the media, improving teacher quality, and providing media is a form of motivational encouragement carried out by the head of the madrasa to his teachers and giving rewards or awards to principals and teachers who carry out their duties properly. (4) the valuation at the Nurmadani NW Montong Lisung Islamic Boarding School is carried out through work meetings or deliberations which are held every 6 months and at the end of the school year involving all concerned at the Islamic boarding school.